PENINGKATAN KREATIVITAS MENGGAMBAR MELALUI POLA BENTUK (SHAPE) - Hidayati, Nurul; Permata, Rista Dwi (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Based on the report of study and survey results, there were still problems that were found when drawing activities, including the process of children learning to draw freely given, so students had difficulty drawing according to the object. Many methods or techniques that can be practiced by the teacher motivate students to increase their creativity to make images into a form of image similar to the object.The method that is suitable for researchers to use is class action research or class action research entitled "Efforts to increase creativity in drawing through shape patterns". The implementation of this research in the DC-PG-TK Plus At Taqwa Brondong Lamongan institute, 2018/2019 education year, using the sample or subject of research is the Group B2 / Al Muqiit class.After conducting research consisting of 2 cycles and achieving an increase and increasing the results the percentage achieved was 55.55% to 92. 59%, therefore drawing activities that use the shape pattern method can improve the ability to draw in children, can foster children's motivation and enthusiasm , children's drawing creativity can increase.